Progression of retinitis pigmentosa on multimodal imaging: The PREP‐1 study. (2nd January 2019) - Iftikhar, Mustafa; Usmani, Bushra; Sanyal, Abanti; Kherani, Saleema; Sodhi, Simrat; Bagheri, Saghar; Schönbach, Etienne M.; Junaid, Nadia; Scholl, Hendrik P. N.; Shah, Syed M. A.
Abstract: Importance: It is important to establish reliable outcome measures to detect progression in retinitis pigmentosa (RP). Background: To evaluate progression of RP using multimodal imaging, including spectral‐domain optical coherence tomography (SD‐OCT), fundus autofluorescence (FAF) and microperimetry (MP). Design: Retrospective longitudinal study at a tertiary teaching hospital. Participants: 205 eyes of 106 patients with RP with 1 to 5 y of follow‐up. Methods: Demographics and visual acuity (VA) were recorded, and each modality was graded at baseline and every annual follow‐up. SD‐OCT was graded for the width of ellipsoid zone (EZ), FAF was graded for the diameter and area of the hyperautofluorescent ring (if present), and MP was graded for mean, central and paracentral sensitivity. Spearman's correlation was used to measure correlations at baseline. Mixed effects models were used to estimate the annual change of each parameter, adjusted for disease duration. Main Outcome Measures: Rate of progression. Results: The median VA at baseline was 75 letters and was positively correlated with mean and central sensitivity ( r : 0.372 and 0.394; P = 0.01 for both). All parameters (except paracentral sensitivity) were strongly correlated with each other ( r : 0.673‐0.991; P < 0.001 for all). The annual rates of change for each parameter were as follows: VA, −2.3 letters ( P < 0.001); EZ, −151 μm ( P < 0.001); ring diameter, −132 μm ( P < 0.001); ring area, −0.4 mm 2 ( P < 0.001); mean sensitivity, −0.3 dB ( P < 0.001); central sensitivity, −0.7 dB ( P < 0.001); paracentral sensitivity, −0.4 dB ( P < 0.001). Conclusions and Relevance: Structural and functional measures are well correlated in RP and can reliably measure disease progression within the course of a year.